Strategi Penerapan Sistem Keamanan Pada Desain Lembaga Pemasyarakatan Kelas II Di Surakarta - Reysa Yanarsya; Rachmadi Nugroho; Agung Kumoro Wahyuwibowo (ARSITEKTURA, 2019)
The role of level II prison in Surakarta as a supporter of the correctional system is based on three aspects. The first aspect is to overcome the problem of prisoners' excess capacity in Indonesia by building prisons in every district or city so that the handling and placement of prisoners are at their place of origin. Second, Surakarta is a city that contributes to the second highest crime rate  in Central Java and the lack of optimal correctional facilities that already exist. Third, the security aspects are the most important factor in establishing prison buildings, because in this era, security is not only done manually but also electronically. The combination of the two security systems can provide the concept of a more modern prison design. The discussion method applied from the beginning to the completion of the design is through the stages of problem identification and exploration, stages of data collection through precedent studies, interviews, observations, and security system theory literature. Then the analysis stages that combine data obtained with theories related to prison buildings. The results of the overall analysis include five concepts of designing prison security system design concepts in the form of deter, detect, delay, halt, and minimize.